Combinatorial Synthesis of Novel 3/5(3,5)-(Di)nitro/chloropaeonol Carbonyl Hydrazone Derivatives as Nematicidal Agents - Chen, Genqiang; Zhu, Lina; Xia, Yanfei; Yang, Jinming; Zhang, Song; Li, Yuanhao; Guo, Xiaolong; Sun, Di; He, Jiaxuan; Tian, Yuee; Liu, Shengming; Jiang, Jia; et al. (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Developing the high-efficiency and low-risk small-molecule greennematocide is the key of effective control of the nematodes. Paeonol, is a naturally occurring phenolic compound, isolated from the root bark of Paeonia suffruticosa and the whole plant of Cynanchum paniculatum. Due to its crucial phenolic ketone skeleton, modern biological science research has indicated that paeonol has a wide range of biological activities. Methods: The structural modification of paeonol into paeonol carbonyl hydrazone derivatives is a potential approach for the development of novel nematodes, which showed more toxicity than paeonol. However, there are no reports on the nematicidal activity of paeonol carbonyl hydrazone derivatives to control Heterodera glycines. Results: We always endeavor to discover and develop biorational natural products-based pesticidal agents, 4 significant intermediates and 21 novel 3/5(3,5)-(di)nitro/chloropaeonol carbonyl hydrazone derivatives were prepared, and their structures well characterized by 1H NMR, HRMS, MS, and mp. Due to the steric hindrance, the substituents on the C=N double bond of all hydrazine compounds adopted E configuration. Results of nematicidal activity revealed that, among all compounds, especially 5-nitropaeonol (5) and 3,5-dinitropaeonol (7) displayed the most potent nematicidal activity H. glycines in vivo with LC50 values of 0.0323 and 0.0367 mg/mL, respectively. Conclusion: It suggested that for the 3/5(3,5)-(di)nitro/chloropaeonol carbonyl hydrazone derivatives, a nitro group introduced at C5 position of 1 was necessary for obtaining the potent compound as nematicidal agents. These preliminary results will pave the way for further modification of paeonol in the development of potential new nematicides.
Keywords: hydrazine